Nutritional profile of kian marine worm from kei islands maluku as a potential high protein food resource - Siti Rahma Lestaluhu; Siti Nur Arifah; Umie Lestari; Sri Rahayu Lestari (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2020)
The nutritional content of kian marine worm has never been reported. This study aimed to profile the nutritional content of worms from the Kei Islands, Maluku. Nutritional profiles were tested by proximate assays, atomic absorption spectroscopy (AAS), and High-Performance Liquid Chromatography (HPLC) of amino acids. The proximate analysis resulted in 71.16% of protein, 12.05% of water, 2.63% of carbohydrates, 2.21% of fat, 2.14% of crude fiber and 0.44% of ash. Mineral contents of Kian marine worm were 785.28 mg/kg potassium, 585.14 mg/kg magnesium, 180.98 mg/kg calcium, 0.89 mg/kg sodium and 0.44 mg/kg phosphorus. Kian marine worms contained 9 essential amino acids and 11 essential amino acids with levels of essential amino acids up to 206.94 mg/g and non-essential amino acids was 233.21 mg/g. Nutritional content in kian marine worms can be used as a potential high protein food resource.